Groundwater head responses to droughts across Germany - P. Ebeling; A. Musolff; R. Kumar; A. Hartmann; J. H. Fleckenstein; J. H. Fleckenstein (Hydrology and Earth System Sciences, 2025)
Groundwater is a crucial resource for society and the environment, e.g., for drinking-water supply and dry-weather stream flows. The recent severe drought in Europe (2018–2020) has demonstrated that these services could be jeopardized by ongoing global warming and the associated increase in the frequency and duration of hydroclimatic extremes such as droughts. To assess the effects of meteorological variability on groundwater heads throughout Germany, we systematically analyzed the response of groundwater heads at 6626 wells over a period of 30 years. We characterized and clustered groundwater head responses, quantified response timescales, and linked the identified patterns to spatial controls such as land cover and topography using machine learning. We identified eight distinct clusters of groundwater responses with emerging regional patterns. Meteorological variations explained about 50 % of the groundwater head variations, with response timescales ranging from a few months to several years between clusters. The differences in groundwater head responses between the regions could be attributed to regional meteorological variations, while the differences within the regions depended on local landscape controls. Here, the depth to groundwater best explained the timescale of the observed head response, with shorter response times in shallower groundwater. Two of the clusters showed consistent long-term trends that were not explained by meteorological controls and could be attributed to anthropogenic impacts. Our study contributes to a better understanding of the regional controls of groundwater head dynamics and to the classification of groundwater vulnerability to hydroclimatic extremes.